Influence of Contrast Agent Injection Scheme Customized by Dual-Source CT Based on Automatic Tube Voltage Technology on Image Quality and Radiation Dose of Coronary Artery Imaging - He, Weiling; Chen, Xin; Hu, Rui; Sun, Wenjie; Tan, Weili (Frontiers in Surgery, 2022)
Objective: To explore the influence of contrast agent injection scheme customized by Dual-source CT based on automatic tube voltage technology on coronary imaging image quality and radiation dose. Methods: 205 patients who underwent coronary CT angiography (CCTA) in our hospital from June 2021 to September 2021 were selected. According to different contrast agent injection schemes, 105 patients in the control group were divided into routine scanning according to body mass, and 100 patients in the observation group were set with tube voltage and contrast agent dosage according to automatic tube voltage selection technology. The CT values of aortic root (AO), left anterior descending branch (LAD), proximal, middle and distal segment of right coronary artery (RCA) and proximal and distal segment of left circumflex branch (LCX) were measured. Calculate the signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) of the image. Image quality score and effective dose (ED) calculation are performed. Results: There was no significant difference in CT values of AO, LAD, RCA and LCX between the two groups (P>0.05). Compared with CNR of LAD, RCA and LCX, there was no significant difference between the two groups (P>0.05). There was no significant difference in image quality scores between the two groups (P>0.05). The dosage of contrast agent and ED in observation group were lower than those in control group (P<0.05). Conclusion: The contrast agent injection scheme customized by Dual-source CT based on automatic tube voltage technology can meet the clinical requirements of coronary imaging image quality, reduce the radiation dose and contrast agent consumption, and help doctors choose a more accurate and reasonable examination scheme, which has certain clinical application value.